2009
DOI: 10.12968/bjom.2009.17.4.41670
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' perspectives on breastfeeding: ideas for intervention

Abstract: This article presents the findings of a small-scale qualitative study with fathers which was part of a larger social marketing project focusing on increasing rates of exclusive breastfeeding in Brighton and Hove. In-depth semi-structured interviews were used to explore fathers' experiences during the pregnancy, birth and up to the first year. Findings revealed a number of potential areas which may be of use to midwives, health visitors, and other health professionals to increase the initiation and continuance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 20 publications
6
95
0
2
Order By: Relevance
“…Without fathers' support, mothers are more likely to breastfeed for a shorter duration [17,18]. When fathers are not supportive, breastfeeding rates are lower [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without fathers' support, mothers are more likely to breastfeed for a shorter duration [17,18]. When fathers are not supportive, breastfeeding rates are lower [19].…”
Section: Introductionmentioning
confidence: 99%
“…Without fathers' support, mothers are more likely to breastfeed for a shorter duration [17,18]. When fathers are not supportive, breastfeeding rates are lower [19].Some authors have suggested that the baby's father is one of the most influential persons to the mother decisions and actions, and that he can act as either key supporter or deterrent to the breast-feeding process [20]. However, many fathers lack the awareness of their relevance to breastfeeding success.…”
mentioning
confidence: 99%
“…In a Finnish study of first-time mothers, mothers cited fathers as the most important member of her breast-feeding support team (16) . Despite the recognized role of fathers in breast-feeding, little is known about the specific support needed and desired by breast-feeding mothers from fathers (17,18) . The aim of the present study was to examine mothers' experience of support received from fathers for breast-feeding.…”
mentioning
confidence: 99%
“…There is strong empirical evidence that the support of a woman's partner is crucial to her breastfeeding success (Scott, Binns, Oddy, & Graham, ). While fathers are typically encouraging of breastfeeding, they often do not know the kinds of emotional and practical support they can provide their partner and feel powerless to help (Sherriff, Hall, & Pickin, ). Fathers are encouraged to attend antenatal classes; however, the level and quality of breastfeeding information provided is often variable and the role of the father either not discussed or glossed over.…”
Section: Supporting the Supporter: Milk Man A Breastfeeding Smartphomentioning
confidence: 99%
“…Fathers are encouraged to attend antenatal classes; however, the level and quality of breastfeeding information provided is often variable and the role of the father either not discussed or glossed over. Furthermore, access to antenatal classes may be restricted to fathers due to the times that they are conducted (Sherriff et al, ).…”
Section: Supporting the Supporter: Milk Man A Breastfeeding Smartphomentioning
confidence: 99%